What we need to do now For a Zero Carbon Future - Chris Goodall (London Profile Books, 2020)
The UK has declared a 'climate emergency' and pledged to become carbon neutral by 2050. So how do we get there? Drawing on actions, policies and technologies already emerging around the world, Chris Goodall sets out the ways to achieve this. His proposals include
Includes bibliographical references and index
Keywords: Sustainability; Green technology; Pollution prevention; Environmental policy